Perceiving blocks of emotional pictures and sounds: effects on physiological variables - Brouwer, Anne-Marie; Van Wouwe, Nelleke; Muehl, Christian; Van Erp, Jan B.; Toet, Alexander (Frontiers in Human Neuroscience, 2013)
Most studies on physiological effects of emotion inducing images and sounds examine stimulus locked variables reflecting a state of at most a few seconds. We here aimed to induce longer lasting emotional states using blocks of repetitive visual, auditory and bimodal stimuli corresponding to specific valence and arousal levels. The duration of these blocks enabled us to reliably measure heart rate variability as a possible indicator of arousal. In addition, heart rate and skin conductance were determined without taking stimulus timing into account. Heart rate was higher for pleasant and low arousal stimuli compared to unpleasant and high arousal stimuli. Heart rate variability and skin conductance increased with arousal. Effects of valence and arousal on cardiovascular measures habituated or remained the same over 2-minute intervals whereas the arousal effect on skin conductance increased. We did not find any effect of stimulus modality. Our results indicate that blocks of images and sounds of specific valence and arousal levels consistently influence different physiological parameters. These parameters need not be stimulus locked. We found no evidence for differences in emotion induction between visual and auditory stimuli, nor did we find bimodal stimuli to be more potent than unimodal stimuli. The latter could be (partly) due to the fact that our bimodal stimuli were not optimally congruent.